Branding Universities: Trends and Strategies - Drori, Gili (International Higher Education, 2013)
Branding campaigns, in which universities restyle their traditional insignia into logos, have both strategic and cultural dimensions. Strategically, rebranding is linked with the expanding efforts of universities to market their programs to prospective students and donors and leverage their reputation for such marketing. Culturally, rebranding symbolically captures the transformation of university governance from guild-like autonomy to a managed and promotional university. The essay describes the three main trends in the branding of universities and considers that strategic implications and cultural meanings of university branding.